Approaches to university management, governance and strategy: systematic literature review in the 21st century - Mosquera-Guerrero, Andrea; Meliá-Martí, Elena; Romero-Torres, Efrén (Revista Venezolana de Gerencia, 2024)
The university is a key actor in the creation of knowledge that must respond to global transformations by meeting the demands of different interest groups, which has led to its management becoming a complex activity. The aim of this paper is to present the trends in university governance, strategy and management through the review of the Clarivate-Web of Science (WOS) and Scopus databases with the support of Vosviewer software. The results have made it possible to identify three perspectives: a) governance and leadership models, b) student body in university governance, quality of service and student entrepreneurship, and c) technology in higher education. For its part, the United Kingdom stands out as the country with the highest scientific production in this area. Finally, the study allows us to conclude that the changes that university management systems have undergone and the relevance that elements such as ICTs, the relationship with business, peer review processes and student participation have acquired within it, reflecting the most relevant factors of the evolution of governance systems in connection with the new dynamics that will guide us towards an entrepreneurial university.